Effects of zeranol and A, D and E vitamins on performance of Guzerá and crossbred with European cattle - Vieira, Paulo de Figueiredo; Moraes Sampaio, Alexandre Amstalden; Tosi, Hugo; de Andrade, Pedro; Favoretto, Vanildo; de Oliveira, Mauro Dal Secco (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was conducted at the feedlot Unit of the Faculdade de Ciências Agrárias e Veterinárias, Campos of Jaboticabal, of the UNESP, with the objective of evaluating the effects of the A, D and E vitamins, on the performance of Guzerá and crossbreds European x Guzerá, and the possible effects on dry matter intake, crude protein intake, gross energy intake and feed conversion. The analysis was completed according to a completely randomized block design in a 2 x 3 factorial with two genetic types (Guzerá and European x Guzerá crossbreds) and three treatments (0, 5.0 ml of A, D and E vitamins/animal, and 36.0 mg of zeranol/animal), with five replications. The zeranol implant improved the weight gains about 10.9%. The application of A, D and E vitamins did not increase the weight gain (P > 0.05). The crossbred animals consumed significantly (P < 0.05) more feed per weight gain unit than Guzerá cattle.